CREATION OF A COSMETIC FOR INTIMATE HYGIENE - KACHAN, ROMAN; DROZDENKO, VITA; KOROLENKO, JULIA; ZAHAREVICH, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The work substantiates the feasibility of creating a cosmetic product for intimate hygiene. This will allow you to get a product that will delicately wash and sanitize intimate areas. In order to have a mild effect on the mucous membranes of the new product, it did not use classic anionic surfactants, which are used in the vast majority of cosmetics with cleansing properties. They were replaced with non-ionic and amphoteric surfactants of plant origin. Also, the pH of the new product is as similar as possible to the pH of the mucous membranes of the reproductive system, which will ensure maximum compatibility. For this purpose, lactic acid was added to the composition of the cosmetic product. In addition, the composition of the developed cosmetic product contains 2 phenoxyethanol. This component is used as a preservative in cosmetics and can also give them a certain antimicrobial activity. This property will help control the amount of microflora of the reproductive system at the proper level. The product also includes such an important component as panthenol. (provitamin B5). This is a derivative of pantothenic acid, which maintains a healthy skin condition. D-panthenol is used in cosmetics, which has the highest biological activity. After application, it is converted into pantothenic acid, stimulating regeneration and moisturizing the skin. Products with panthenol soothe irritation, reduce redness and relieve symptoms of discomfort in intimate areas, restore the skin after aggressive procedures (peeling, laser therapy) and strengthen its natural protective barrier. In order to accelerate the regeneration of mucous membranes, to give the product antioxidant properties, chamomile extract was added to the composition of the cosmetic product. It also stimulates cell renewal and metabolic processes in the dermis. Thus, a cosmetic product was created that has cleansing and moderate antimicrobial properties, regenerating ability.
Keywords: cosmetic product for intimate hygiene; surfactant; 2 phenoxyethanol; cleansing properties